Efficient Eye Blink Detection for Disabled - S, Aishwarya; GN, Amulya; N, Anusha; Kamath, Anvitha; S, Sushmitha (International Journal of Computer Sciences and Engineering, 2020)
This paper proposes the concept of Machine Learning to implement an eye blink detection system. It is used to first track the eyes on the patient and then detect its movements. Machine learning has experienced a boost in acceptance among many fields including the medical field. People suffering from speech impairment find it difficult to communicate their needs to the outside world. People with severe disabilities are confined in a state in which communication is virtually impossible, being reduced to communicating with their eyes or using sophisticated systems that translate thoughts into words. The Eye Trackers are suitable systems for those people but the main disadvantage is the cost. More affordable devices are capable of detecting voluntary blinks and translating them into a binary signal that allows the selection. The method of voluntary blinking, the use of long or double blinks had no statistical influence on accuracy, excluding EOG, and the time taken to perform double blinks was shorter, resulting in a potentially much faster interface. Machine learning creates a platform to be precise in the measurement of any parameters using various algorithms. In this paper, we propose to apply Haar cascade and shape predictor algorithms to map the eyes of the patient and detect various blink patterns. The preferred technology and blinking methods were Video-Oculography (VOG) and long blinks Implementation of this paper successfully bridges the communication gap between the outside world and the paralyzed/disabled patients.